Perceptual Hypnosis: A Spiritual Journey Toward Expanding Awareness by Dr. Frederick Woodard - Epstein, Flavio Rose (Journal of Scientific Exploration, 2018)
Division 30 of the American Psychological Association (APA) defines hypnosis as: “A state of consciousness involving focused attention and reduced peripheral awareness characterized by an enhanced capacity for response to suggestion.” Yapko (2012) writes that “the field of hypnosis has been influenced by the need for empirically validated treatments” (p. 10). Hypnosis has been associated with improved perceived stress (Fisch 2017), and the lowering of pain, nausea, and fatigue (Montgomery 2007). In a meta-analysis, hypnosis has been established as adjunctive treatment to medical and psychological interventions, increasing treatment efficacy (Mendoza & Capafons 2009). Empirically supported hypnosis scripts have been organized in a hypnosis medical manual for practicing hypnotherapists (Elkins 2017). Cutting-edge research, evaluating physiological changes in the brain, during hypnosis, led by senior Stanford researcher, Dr. David Spiegel (Jiang 2016), used fMRI (functional magnetic resonance imaging) during hypnosis, and found changes in neural activity. Part of the conclusion summary reads: “These changes in neural activity underlie the focused attention, enhanced somatic and emotional control, and lack of self-consciousness that characterizes hypnosis.” Grounded in phenomenological–perceptual theory, and building on Jung’s (1971) and Erickson’s (1980) work, among others, Dr. Woodard writes about the effects of hypnosis in the conscious and in the unconscious mind. Perceptual Hypnosis: A Spiritual Journey Towards Expanding Awareness includes an introduction, eleven chapters, and a conclusion, which provide a method and tools for self-help. At the end of each chapter, a summary of the main perceptual points and exercises to guide self-inquiry assist the reader in applying and deepening the learned content. The accompanying CD provides self-help recorded instruction for self-exploration. Dr. Woodard outlines the foundational experiential and theoretical elements that led to the writing of his book, including his own experience undergoing various hypnotic experiences, and he theoretically proposes that hypnosis consists of differentiation, where certain aspects of the perceived Universe are magnified, while others settle in the background. He hypothesizes that hypnosis works within three levels of awareness, including a higher self, a conscious mind, and a subconscious mind, stating that “perceptual hypnosis is a spiritual phenomenon” (p. 52).